Transformations of Religion and the Public Sphere
X, 281 p.
Keywords: Religion-fuelled terrorism and attacks on freedom of expression have recently drawn headlines across Europe, either in protest or in support of extreme political or religious persuasions. This books explores interdisciplinary perspectives on public discussions of liberal-secular freedoms and their implications in a postsecular world.